Effects of compression running pants and treadmill running stages on knee proprioception and fatigue-related physiological responses in half-marathon runners - Chang, Lin; Fu, Silin; Li, Jianghua; Wu, Sam; Adams, Roger; Han, Jia; Han, Chunying (Frontiers in Physiology, 2022)
Background: Knee injury is common in half-marathon runners, however, the effect of compression running pants on fatigue and knee proprioception remains unclear. Objectives: The study aims to investigate whether wearing CRP and treadmill running stages affect knee proprioception and fatigue-related physiological responses physiological responses during half-marathon running. Methods: Eighteen half-marathon runners completed two self-paced 21km treadmill running trials, once wearing CRP and once wearing loose running shorts (LRS). For each 21km run, RPE, heart rate, blood lactic acid, and knee flexion proprioception were assessed before starting, and after each 7km stage. Results: Data analysis revealed no difference between CRP and LRS conditions in heart rate, RPE, or blood lactic acid. Repeated measures ANOVA showed a significant garment condition main effect whereby wearing CRP was associated with higher knee proprioceptive acuity (p=0.006). Polynomial trend analysis showed a significant linear downwards trend in proprioceptive acuity across the four measurement occasions (p=0.048). Stage analysis showed that wearing CRP was associated with better knee proprioception at running distances of 14km (p=0.007, 95%CI =-0.054, -0.010) and 21km (p=0.016, 95%CI = -0.051, -0.006). Conclusions：CRP provides an overall positive effect on knee proprioception, particularly after 14km and 21km, which may reduce the probability of knee injury. CRP had no significant effect on physiological measures in half-marathon running.